Analisis Resepsi Pesan Gambar Peringatan Di Kemasan Rokok Di Kalangan Mahasiswi Kota Bandung - Natakusumah, Ibnu Arkaan; Dimyati, Dindin (eProceedings of Management, 2024)
The purpose of this research is to analyze the reception response of female smokers in the city of Bandung regardingwarning images on cigarette packaging using Stuart Hall's Reception Analysis theory to see the audience's responseand interpretation in receiving a message, then the audience's message reception is identified from the receptionanalysis theory, namely Hegemonic Dominant Position, Negotiated Position, and Opposition Position. In thisresearch, the researcher used a qualitative phenomenological method with the object of warning images on cigarettepackaging and female students who smoked, then collected data using open and semi-structured interview methods,documentation, and Audio Visual Material by Creswell. The results of the research showed that there were informantswho received the warning image message on the packaging in full, the informant felt the effects of fear and wasworried that they would contract a disease such as in the warning image on the cigarette packaging if they did notstop consuming cigarettes (Hegemonic). Then there are informants who negotiate and adapt the message of warningimages on cigarette packaging to their own experiences, there is an interpretation which states that cigarette warningimages are considered not enough to make smokers quit, warning images on cigarette packaging only discourageaudiences who do not consume cigarettes, then the interpretation regarding The victims visualized on cigarettepackaging are smokers who have been dependent for a long time and consume excessive cigarettes (negotiated). Therewas no rejection of messages found in the warning images on cigarette packaging (Opposition). Keyword-reception analysis, smoking student, message, pictorical health warning cigarette packages.